2017
DOI: 10.1002/clc.22685
|View full text |Cite
|
Sign up to set email alerts
|

Coronary artery calcification is common on nongated chest computed tomography imaging

Abstract: Background Coronary artery calcification as assessed by computed tomography (CT) is a validated predictor of cardiovascular risk, whether identified on a dedicated cardiac study or on a routine non‐gated chest CT. The prevalence of incidentally detected coronary artery calcification on non‐gated chest CT imaging and consistency of reporting have not been well characterized. Hypothesis Coronary calcification is present on chest CT in some patients not taking statin therapy and may be under‐reported. Methods Non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 14 publications
1
9
0
1
Order By: Relevance
“…Meanwhile, up to 19 million non-gated chest CT scans were performed in 2014 alone for non-cardiac indications 18 , 46 . Though these exams may demonstrate coronary calcification, up to 80% of radiologist reports do not mention it 47 , 48 . Even if radiologists report incidental coronary calcification, accurate quantitation is difficult as no widely accepted standard currently exists unlike scoring using gated coronary CT.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, up to 19 million non-gated chest CT scans were performed in 2014 alone for non-cardiac indications 18 , 46 . Though these exams may demonstrate coronary calcification, up to 80% of radiologist reports do not mention it 47 , 48 . Even if radiologists report incidental coronary calcification, accurate quantitation is difficult as no widely accepted standard currently exists unlike scoring using gated coronary CT.…”
Section: Discussionmentioning
confidence: 99%
“…A survey of 200 United Kingdom radiologists found that 11 % never reported the presence of calcification in the coronary arteries and the radiologists who were not sub-specialists in cardiac imaging were less likely to report calcification in the coronary arteries [45]. Other studies show that incidental calcification in the coronary arteries is not mentioned on between one quarter and one fifth of thoracic CT reports [27,28,46,47]. Automated assessment of calcification on thoracic CT using machine learning techniques may aid the speed and accuracy of radiologist reporting [48].…”
Section: What Is Coronary Artery Calcification?mentioning
confidence: 99%
“…La presencia de calcificaciones debe informarse con regularidad, sobre todo en pacientes jóvenes (< 55 años en hombres y < 65 años en mujeres) en quienes puede ser un indicador de enfermedad coronaria prematura. Es difícil calcular el grado de estenosis relacionada en un estudio sin sincronización cardíaca, aun cuando sea contrastado, por lo cual es recomendable abstenerse de proporcionar una cifra aproximada, a menos que sea muy evidente 1,9,10 .…”
Section: Arterias Coronarias: Calcificaciones/anomalías De Origen O Trayecto/aneurismaunclassified